Talent Management: A study of Indian IT Companies in NCR - Singh, Dr. Uma S. (The journal of contemporary issues in business and government, 2019)
Organizations today have realized the significance of human assets and no organization can achieve great success without talented employees. It is the skilled and competent employees that make the organizations and they are not only to be procured but also need to be retained and sustained. Industries operating in highly volatile and dynamic environments, requiring skilled and competent workforce becomes a challenge itself, especially for the IT sector. Hence there is a need to focus on what practices and strategies can be adopted to attract and retain potential key talent. The study aims is to identify talent retention strategies that are adopted in the IT sector in India and to determine the reasons for talent management strategies and their efficiency thereof. This will help us understand the key drivers of employees’ intentions to stay in their current organization based on TM’s strategies. The present work is empirical in nature and the data was collected from a randomly drawn group of 185 IT professionals working in IT companies in Noida, and Gurgaon. Delhi NCR is fast emerging as India’s foremost IT destination. Mean and independent sample t-tests were applied for the purpose of data analysis and interpretation. The results of the study highlight salary & incentives and work life balance as the key strategies for talent retention. The main reason that emerged for TM is its upmost importance for the business to be successful and sustain well in a turbulent environment like the IT sector.